Association of rs865429 C/T polymorphism in SOST gene with Coronary Heart Disease in Iraqi Type 2 Diabetes Mellitus Patients - Ruaa Ali Mohammed Ali1 , Rasha Shaker Nima2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Sclerostin, encoded by the SOST gene, It has also been shown that sclerostin is expressed in aortic VSMC(vascular smooth muscle) and upregulation of SOST gene has inhibitory effects on the aortic aneurysmand atherosclerosis development. Aims: The current study aims to explore potential the associationbetween SOST gene single nucleotide polymorphisms (rs865429 C/T) and coronary artery diseases (CHD)in type 2 diabetes mellitus (T2DM) patients, in addition to the effect of this SNP on the level of serumsclerostin and other glycemic parameters. Material and methods: From the Iraqi population, we enrolled300 T2DM patients (150 T2DM with CHD and 150 T2DM without CHD). Serum blood glucose, seruminsulin, HbA1C, and sclerostin were estimated. Genotyping for rs865429 C/T in SOST gene was achievedby RFLP (polymerase chain reaction-restriction fragment length polymorphism). Results: T2DM patientshaving CT + TT genotype included in the studied were at increased risk for CHD in T2DM (odd ratio:0.4444 CI: 0.2800 to 0.7054) and related to a high serum sclerostin level in comparison with type 2 diabeticpatients with CC genotype. Conclusions: Type 2 diabetic patients with T allele who have elevated plasmaconcentrations of sclerostin are at high risk for coronary artery diseases.